PENGARUH PELAYANAN GRAB TERHADAP KEPUASAN KONSUMEN PADA MASA PANDEMI COVID-19 DI PURWOREJ (STIE Rajawali Purworejo, 2021)
This research aims to find out whether there is a positive and significant influence between Grab's service quality and consumer satisfaction during the Covid-19 pandemic. The population in this research is Grab users in Purworejo whose number is unknown, while the number of samples in this research is 40 people. Data collection techniques in this research are observation, questionnaires, documentation and literature study. Data analysis techniques use simple correlation tests, simple linear regression, determination tests and t tests. The results of a simple correlation test show that service quality X and customer satisfaction Y have a significance value of 0.659, which means that the two variables have a strong correlation. Based on a simple linear regression test, the resulting regression coefficient X is 0.410, which states that if there is an increase of 1 point in the value of the regression coefficient The results of the determination test showed that the coefficient of determination (R2) had a value of 0.435, this means that 43.5% of consumer satisfaction was influenced by the service quality variable, while 56.5% was influenced by other variables that were not studied, for example competition with other online motorcycle taxis, tariffs. or price, customer experience in using grab services, etc. Based on the t test, tcount is 5.408 while ttable is 2.02439. With these data, tcount > ttable, so it can be concluded that the Ha hypothesis is acceptable, namely that there is a significant influence between service quality variables on customer satisfaction and can be accepted.